2006
DOI: 10.1002/ajmg.b.30397
|View full text |Cite
|
Sign up to set email alerts
|

Exon 3 polymorphisms of dopamine D4 receptor (DRD4) gene and attention deficit hyperactivity disorder in Chinese children

Abstract: Dopamine D4 receptor (DRD4) gene is implicated in the pathogenesis of attention deficit hyperactivity disorder (ADHD). The 7-repeat allele of the variable-number-of-tandem-repeat (VNTR) polymorphism in exon 3 has been reported to be associated with ADHD. However, studies in Chinese populations have yielded conflicting results. We therefore perform another study to investigate the association between ADHD and DRD4 gene polymorphism in Chinese children in Hong Kong. In this prospective family-based and case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…The present meta-analysis included independent data available from 10 TDT (Arcos-Burgos et al 2004a;Brookes et al 2006a;Kustanovich et al 2004;Lunetta et al 2000;Maher et al 2002;Mick et al unpublished data;Sunohara et al 2000;Tahir et al 2000b;Todd et al 2001b) and 16 Case-Control/HHRR (Bakker et al 2005;Carrasco et al 2006;Curran et al 2001a;El-Faddagh et al 2004;Frank et al 2004;Gornick et al 2007;Hawi et al 2000a;Holmes et al 2000;Kotler et al 2000;LaHoste et al 1996;Mill et al 2001;Roman et al 2001;Rowe et al 1998;Smith et al 2003;Swanson et al 1998) studies, with the 7-repeat considered the "high-risk" allele. Two studies in Asian populations could not be included in the meta-analysis, given insuYcient frequencies of the 7-repeat allele (Cheuk et al 2006a;Kim et al 2005b). Results of this meta-analysis, shown in Fig.…”
Section: Dopamine D4 Receptor Gene (Drd4)mentioning
confidence: 99%
“…The present meta-analysis included independent data available from 10 TDT (Arcos-Burgos et al 2004a;Brookes et al 2006a;Kustanovich et al 2004;Lunetta et al 2000;Maher et al 2002;Mick et al unpublished data;Sunohara et al 2000;Tahir et al 2000b;Todd et al 2001b) and 16 Case-Control/HHRR (Bakker et al 2005;Carrasco et al 2006;Curran et al 2001a;El-Faddagh et al 2004;Frank et al 2004;Gornick et al 2007;Hawi et al 2000a;Holmes et al 2000;Kotler et al 2000;LaHoste et al 1996;Mill et al 2001;Roman et al 2001;Rowe et al 1998;Smith et al 2003;Swanson et al 1998) studies, with the 7-repeat considered the "high-risk" allele. Two studies in Asian populations could not be included in the meta-analysis, given insuYcient frequencies of the 7-repeat allele (Cheuk et al 2006a;Kim et al 2005b). Results of this meta-analysis, shown in Fig.…”
Section: Dopamine D4 Receptor Gene (Drd4)mentioning
confidence: 99%
“…Five studies conducted with Asian populations were excluded due to the absence of 7R alleles [Qian et al, 2004;Brookes et al, 2005;Kim et al, 2005;Leung et al, 2005;Cheuk et al, 2006]. Four studies were excluded because the OR corresponding to the association between the 7R allele and AD/HD could not be computed [Manor et al, 2002;Bhaduri et al, 2006;Brookes et al, 2006;Monuteaux et al, 2008].…”
Section: Identified Studiesmentioning
confidence: 99%
“…It is important to study the human dopaminergic system because it has shown its involvement in different neuropsychiatric and personality disorders (Cheuk et al, 2006;Hoenicka et al, 2007). Study of this locus has direct relevance in the field of neurology, psychology, endocrinology, and pharmacology (Aguirre-Samudio and Nicolini, 2005;Aguirre et al, 2007;Mandelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%